2021
DOI: 10.3390/buildings11020051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Legal Framework for Building Fire Safety Regulations in Spain

Abstract: There is a trend in Europe towards increasing the quality and performance of regulations. At the same time, regulatory failure has been observed in the area of building fire safety regulation in England and elsewhere. As a result, an analysis of the appropriateness of fire safety regulations in Spain is warranted, with the objective being to assess whether a suitable level of fire safety is currently being delivered. Three basic elements must be considered in such analysis: the legal and regulatory framework, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Moreover, the fire is highly likely to develop into a large-scale fire when it starts in a closed space. Australia, China, and the UK have recently increased their level of awareness of the fire risks in major buildings in relation to highly flammable exterior cladding panels [35][36][37].…”
Section: Results Of Fire Safety Expert Surveymentioning
confidence: 99%
“…Moreover, the fire is highly likely to develop into a large-scale fire when it starts in a closed space. Australia, China, and the UK have recently increased their level of awareness of the fire risks in major buildings in relation to highly flammable exterior cladding panels [35][36][37].…”
Section: Results Of Fire Safety Expert Surveymentioning
confidence: 99%
“…In advanced countries also, regulatory failure has also been observed in building fire safety regulations. Across Europe, Osácar et al (2021) concluded that the analysis of legal and regulatory framework, the expected level of fire risk/safety of buildings and actual fire safety achieved or implemented constitutes the basic framework for determining the appropriateness of fire safety regulations. While fire continue to raze buildings in the congested urban areas of both developed and developing nations, practically nothing is known about the peri-urban neighbourhoods that have been witnessing rapid physical transformation in the past two to three decades with regard to the level of compliance with safety standards or the appropriateness of the safety codes in recent times.…”
Section: 10 Introductionmentioning
confidence: 99%